Burnout en profesionales de establecimientos de salud del primer nivel de atención de Lima Metropolitana - Nunura Linares, Luis Ernesto (2016)
The present research is about the burnout´s syndrome and its presence in health professionals in metropolitan Lima Polyclinics. The reasons that drive this study are based on concerns about the increasing number of people with the syndrome and the limited research in the health area that can be applied to peruvian context. This research focused on finding and describing levels of Burnout´s syndrome in a sample of 85 doctors and 41 nurses, who were assessed with the Maslach Burnout Inventory adapted to peruvian context by Victoria Llaja in 2007. The research is descriptive comparative and has a quantitative approach. The sample was selected on a non-probabilistic way and by convenience. Besides finding Burnout levels in participants, comparisons were made between the three scales of Burnout, (Emotional Weariness, Selflessness, Reduction of the personal Accomplishment) based on gender, profession, years of service and hours of work per week. The results prove the presence of the syndrome in the study sample and justify the need to intervene in these professionals, providing them with strategies to face with the demands required by their professions and for improvements in health institutions.